Optical features of linear Fresnel collectors with different secondary reflector technologies. (15th December 2018) - Abbas, R.; Sebastián, A.; Montes, M.J.; Valdés, M.
Highlights: Different secondary reflector technologies for linear Fresnel collectors are compared. Optical annual performance is analyzed in selected ranges of the design variables. Efficiency, mean flux intensity and mean flux intensity uniformity are studied. Compound parabolic concentrators achieve more homogeneous fluxes. Adaptive design concentrators achieve higher efficiencies for vacuum absorbers. Abstract: This paper is devoted to the analysis of different secondary reflector designs for linear Fresnel collectors. A number of authors have proposed alternative shapes of secondary reflectors in order to enhance the efficiency and the flux intensity at the absorber tube. In this work the primary mirrors layout has been maintained constant for all designs. Thus, only secondary concentrators that do not require a change in the primary mirrors field have been studied. In order to carry out the study a validated Monte Carlo ray trace code has been used, where three optical properties are considered: annual optical efficiency, mean flux intensity and circumferential flux intensity homogeneity. The maximum efficiency reached by each technology, for given optical flux specifications, is obtained. Finally, the optical performance of linear Fresnel collectors with secondary reflector is compared with that of state-of-the-art parabolic trough collectors. It is concluded that the efficiency of Fresnel collectors is around 23% than that of parabolic troughs, although with mean flux intensities around 46% higher and circumferential flux intensities notably more homogeneous (top to bottom flux intensity ratios five times higher).